A STUDY OF EFL TEACHING STRATEGIES IN PESANTREN(A descriptive study in two pesantrens in Bandung) - Elis Suhartini, - (2009)
Mostly in pesantrens, traditional approaches for teaching are used. Therefore this thesis was intended to portray English teaching strategies in pesantren. This study investigated teachers' guiding principles for teaching English, the instructional strategies used by pesantren teachers to teach reading comprehension and vocabulary development and the assessment in Pesantren. The study employed a qualitative design. It used a case study because it was carried out in a small scale that was a single case and it was focused on one particular instance of educational experience and practice, i.e. only in two pesantrens in Bandung. The data were collected trough classroom observation and interview. The data were analysed and interpreted under the theory of teaching reading comprehension, vocabulary development, and the assessment in language teaching. The study shows that knowledge about instructional strategies was important to make the process of teaching and learning more effective and efficient. Based on the findings it is recommended that teachers are given more opportunities to improve their knowledge about new teaching approaches.